1999
DOI: 10.1007/s002340050795
|View full text |Cite
|
Sign up to set email alerts
|

Brain metabolites in the hippocampus-amygdala region and cerebellum in autism: an 1 H-MR spectroscopy study

Abstract: Histological abnormalities of the brain in autism have been investigated extensively. We studied metabolites in the hippocampus-amygdala (HA) region and cerebellum. We examined the right HA region and left cerebellar hemisphere of 27 autistic patients 2-18 years old, 21 boys and 6 girls and 10 normal children 6-14 years old, 4 boys and 6 girls, using the STEAM sequence. This sequence was used to minimise the influence of relaxation times. The N-acetyl aspartate (NAA) concentration was significantly lower (P = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
82
1
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 9 publications
5
82
1
1
Order By: Relevance
“…Significant group differences in individual regions were limited to the left middle frontal gyrus, although the ASD group average was lower than the control group in all the brain regions assayed (frontal, parietal, occipital, and cerebellar) and when all brain areas were averaged, suggesting the possibility of widespread abnormalities. This study extended prior work in this area by establishing that neural abnormalities, which have been identified using 1 H-MRS predominantly in younger and likely lower functioning autistic individuals (Chugani et al, 1999;Friedman et al, 2003;Friedman et al, 2006;Hashimoto et al, 1997;Hashimoto et al, 1995;Hisaoka et al, 2001;Otsuka et al, 1999), may also be present in a higher functioning broadly inclusive ASD sample. None of the individuals in our sample had IQs in the mentally retarded range and the sample included individuals with diagnoses in the less severe end of the autism spectrum; approximately 43% of the sample was diagnosed as PDD-NOS or Asperger's disorder.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Significant group differences in individual regions were limited to the left middle frontal gyrus, although the ASD group average was lower than the control group in all the brain regions assayed (frontal, parietal, occipital, and cerebellar) and when all brain areas were averaged, suggesting the possibility of widespread abnormalities. This study extended prior work in this area by establishing that neural abnormalities, which have been identified using 1 H-MRS predominantly in younger and likely lower functioning autistic individuals (Chugani et al, 1999;Friedman et al, 2003;Friedman et al, 2006;Hashimoto et al, 1997;Hashimoto et al, 1995;Hisaoka et al, 2001;Otsuka et al, 1999), may also be present in a higher functioning broadly inclusive ASD sample. None of the individuals in our sample had IQs in the mentally retarded range and the sample included individuals with diagnoses in the less severe end of the autism spectrum; approximately 43% of the sample was diagnosed as PDD-NOS or Asperger's disorder.…”
Section: Discussionsupporting
confidence: 66%
“…However, inconsistent results have been reported. For example, other studies did not find abnormally reduced levels of NAA in the frontal gray matter (Chugani et al, 1999;Levitt et al, 2003;Otsuka et al, 1999), temporal lobes (Levitt et al, 2003), bilateral thalamus (Levitt et al, 2003) and the amygdala-hippocampal and parietal regions (Page et al, 2006) in autism. These inconsistencies are difficult to interpret because studies differ widely in age range and level of functioning of their participants, and technical methodology.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Given the role of the cerebellum in postural control, it has been suggested that autism is characterised by a visual motion integration impairment, and that this may reflect defective visuo-cerebellar circuitry (Gepner & Mestre, 2002b). Since several neuroimaging (Courchesne, 1997;Otsuka, Harada, Mori, Hisaoka, & Nishitani, 1999) and postmortem studies (Bauman & Kemper, 1994) have shown cerebellar abnormalities in autism, this may represent an anatomical correlate for abnormalities in balance and motor control. A second aspect of this study is therefore to measure fine and gross motor control in children with autistic spectrum disorder, and to investigate whether a relationship exists between the performance of these tasks and tasks of visual motion coherence sensitivity.…”
mentioning
confidence: 99%
“…5 The authors postulated that a hypermetabolic energy state and undersynthesis of brain membranes may underlie this in individuals with autism. Some studies found decreased NAA levels in the hippocampus-amygdala, 6 temporal cortex, 7 and cerebellum 8 of children with autism. Another study reported an association between 1 H-MR spectroscopy Cho/Cr ratios and severity of autism.…”
mentioning
confidence: 99%